1999
DOI: 10.2134/agronj1999.914713x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Tests for Hormesis and Effective Dosages in Herbicide Dose Response

Abstract: [1]The log-logistic model is a popular candidate for modeling dose response in agronomy. One of its limitations is monotonicity: the where E[Y|x] represents the average response at dosage response is either continuously increasing or decreasing with changes x, and ␣ and ␦ are the upper and lower asymptote of in dosage. In herbicide dose response investigations, authors have response, respectively. The parameters and ␤ are repreviously noted an increase in biomass or growth for subinhibitory lated to the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
244
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(257 citation statements)
references
References 27 publications
7
244
0
6
Order By: Relevance
“…All analyses were performed on the data pooled across the two experimental runs as no significant differences were observed between the two runs, based on a sum-of-squares reduction test (Schabenberger et al 1999). Root mean square error (RMSE) values were calculated as…”
mentioning
confidence: 99%
“…All analyses were performed on the data pooled across the two experimental runs as no significant differences were observed between the two runs, based on a sum-of-squares reduction test (Schabenberger et al 1999). Root mean square error (RMSE) values were calculated as…”
mentioning
confidence: 99%
“…For the association of this same dose with phosphite, it was verified significant reduction of plant height, around 54% in relation to the check, evidencing high levels of phytotoxicity. Several papers demonstrate stimulation of plant growth in relation to low doses glyphosate herbicide (Schanbenberger et al, 1999;Wagner et al, 2003;Cedergreen et al, 2007;Velini et al, 2008). Partial blockage of EPSPs, through the application of glyphosate reduced doses, implicated in growth stimulation of various plant species including eucalyptus, pines, maize and soybean (no transgenic and susceptible to glyphosate).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the response had a more pronounced hormetic effect in woody species, such as Eucalyptus spp. Other authors have observed hormesis with glyphosate in maize crops (SCHABENBERGER et al, 1999) and Echinochloa crus-pavonis (WAGNER et al, 2003).…”
Section: Introductionmentioning
confidence: 89%